Algorithm of the longest commonly consecutive word for plagiarism detection in text based document - Sediyono, Agung; Ku-Mahamud, Ku Ruhana (2008)
Plagiarism is a form of academic misconduct which has increased with the easy access to obtain information through electronic documents and the Internet. The problem of finding document plagiarism in full text document can be viewed as a problem of finding the longest common parts of strings.Moreover, the detection system has to be capable to determine and visualize not only the common parts but also the location of the common parts in both the source and the observed document. Unlike previous research, this paper proposes a numerical based comparison algorithm that is comparable in the computation time without loosing the word order of common parts. Based on the experiment, the proposed algorithm outperforms the suffix tree in the length of observed paragraph below one hundred words.